The need for integration of cervical cancer screening into family planning services among women in Ibadan, Nigeria: A cross sectional study. (2024)
Cervical cancer screening (CCS) access has remained a major challenge in developing countries. Integration of CCS into family planning services (FPS) is one strategy that could increase access and uptake of CCS services (CCSS). There are limited data on the integration of CCS into FPS, in Ibadan; hence, this study assessed the need for integration of CCS into FPS in Ibadan, Nigeria. This cross-sectional study was conducted among 202 female family planning clinic attendees selected using purposive sampling technique. A structured interviewer-administered questionnaire was used for data collection. Quantitative data were analyzed using descriptive and inferential statistics at 0.05 level of statistical significance. Mean age of the women was 32.7±6.5 years, 74.3% had poor knowledge of cervical cancer 80.2% had positive perception of the integration of CCS into FPS, 7.4% had utilized CCS, 76.2% were willing to uptake CCSS. There was also a significant association between educational level and knowledge on CCS (p= 0.000); also with the perception of inclusion of CCS into FPS and willingness to utilize CCSS (p= 0.000). The need for integration was evident as the respondents had positive perception of integration of CCS into family planning services.